Unemployment accounts and employment incentives - Alessio J. G. Brown; Jonathan Michael Orszag; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2006)
We explore the far-reaching implications of replacing current unemployment benefit (UB) systems by an unemployment accounts (UA) system. Under the UA system, employed people are required to make ongoing contributions to their UAs and the balances in these accounts are available to them during periods of unemployment. The government is able to undertake balanced-budget interpersonal redistributions among the UAs. At the end of their working lives, people could transfer the remaining balances on their UAs into their pensions. We present an analytical framework to analyse the incentive e.ects of UAs and calibrate our model for the high unemployment countries of Europe. Our results suggest that this policy reform would significantly change people's employment incentives and could achieve reductions in unemployment without reducing the level of support to the unemployed.
Keywords: J32; I38; J68; J38; J64; J65; J22; 330; Unemployment accounts; Redistribution; Employment; Unemployment; Unemployment benefits; Arbeitslosenversicherung; Reform; Vermögensbildung; Wirtschaftspolitische Wirkungsanalyse; Arbeitsangebot; Ökonomischer Anreiz; Theorie; Beschäftigungseffekt; Belgien; Frankreich; Deutschland; Italien; Spanien